Essential Components of Teachers’ Self-Assessment for Professional Development in Indonesia - Rani Martalisa Taorina; Didi Suryadi; Tatang Herman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Teachers’ self-assessment is recognized as a key mechanism for fostering professional growth and improving instructional practices. It allows educators to reflect on and develop their teaching performance autonomously. However, in the Indonesian context, there is a scarcity of self-assessment instruments that are both effective and measurable. This study employed a descriptive qualitative approach with a case study design to analyze existing teacher self-assessment instruments. Indicators from several available tools were examined and categorized using a theoretical framework comprising three core domains: knowledge of content, knowledge of pedagogy and practice, and knowledge of students. The analysis resulted in the identification of seven essential components for teacher self-assessment: (1) connecting students’ prior knowledge with new content; (2) effective delivery of instructional materials; (3) addressing students’ errors, difficulties, and misconceptions; (4) promoting active student participation; (5) building rapport among students and between teachers and students; (6) effective use of learning resources, media, and technology; and (7) selecting, using, and following up on assessments. These components were further structured across three developmental levels to reflect teachers’ growth. The proposed components serve as a foundation for developing more comprehensive and contextually relevant self-assessment instruments for teachers. By aligning self-assessment practices with pedagogical goals and classroom realities, these tools can support sustained professional development and instructional improvement.